Implementasi Model Hybrid Management System Dalam Meningkatkan Efektivitas dan Efisiensi Organisasi Pendidikan - Putri Ananda; Syafa'atul Habib; Ismawati Ismawati; Najma Qurrotul'Aini (JURNAL MANAJEMEN PENDIDIKAN, 2026)
IMPLEMENTATION OF THE HYBRID MANAGEMENT SYSTEM MODEL IN INCREASING THE EFFECTIVENESS AND EFFICIENCY OF EDUCATIONAL ORGANIZATIONS Following the COVID-19 pandemic, educational organizations are required to implement flexible and adaptive work systems to adapt to changes in the work environment and technological developments. The shift from conventional work patterns to the use of digital technology has led to the emergence of a hybrid management system approach, an organizational management system that combines face-to-face and digital-based work. This study aims to examine the implementation of a hybrid management system model in improving the effectiveness and efficiency of educational organizations. This research uses a qualitative approach with a literature review method through a review of scientific journals, books, and relevant sources related to organizational management and hybrid work systems. The results indicate that implementing a hybrid management system can increase work flexibility, optimize technology utilization, and improve coordination effectiveness. However, its implementation still faces challenges, particularly in infrastructure readiness, human resource digital literacy, and performance management systems. Therefore, strategic planning and integrated management support are needed for the optimal and sustainable operation of the hybrid system.